2023
DOI: 10.1111/oik.09801
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effects of stressors on the health, survival and reproduction of a critically endangered, long‐lived species

Abstract: Quantifying the cumulative effects of stressors on individuals and populations can inform the development of effective management and conservation strategies. We developed a Bayesian state–space model to assess the effects of multiple stressors on individual survival and reproduction. In the model, stressor effects on vital rates are mediated by changes in underlying health, allowing for the comparison of effect sizes while accounting for intrinsic factors that might affect an individual's vulnerability and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…The recent plight of NARWs has been well documented by the scientific community thanks to immense efforts by the North Atlantic Right Whale Consortium (NARWC) and its collaborators to monitor the species (e.g., Moore et al, 2021). Stock assessment models using capture-recapture indicate a clear population decline (Pace et al, 2017; Hayes et al, 2022) and individual health assessments with modeling of multiple stressors make clear that anthropogenic threats have been the overwhelming cause of elevated ailments and decreased survival in recent years (Rolland et al, 2016; Knowlton et al, 2022; Pirotta et al, 2023). In addition to direct anthropogenic threats, climate change has altered NARW prey availability and instigated a distribution shift that has likely exacerbated human-caused interactions (Meyer-Gutbrod et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent plight of NARWs has been well documented by the scientific community thanks to immense efforts by the North Atlantic Right Whale Consortium (NARWC) and its collaborators to monitor the species (e.g., Moore et al, 2021). Stock assessment models using capture-recapture indicate a clear population decline (Pace et al, 2017; Hayes et al, 2022) and individual health assessments with modeling of multiple stressors make clear that anthropogenic threats have been the overwhelming cause of elevated ailments and decreased survival in recent years (Rolland et al, 2016; Knowlton et al, 2022; Pirotta et al, 2023). In addition to direct anthropogenic threats, climate change has altered NARW prey availability and instigated a distribution shift that has likely exacerbated human-caused interactions (Meyer-Gutbrod et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We posited that severe injuries observed in live individuals could help indicate the cause of subsequent mortality events, allowing us to leverage the immense monitoring efforts (Hamilton et al, 2007) and health assessments (Knowlton et al, 2016; Pettis et al, 2017) that exist for the species. These monitoring data have been used to model and predict fine-scale changes in NARW health due to multiple stressors (e.g., Knowlton et al (2022); Pirotta et al (2023); and references therein). Here, we integrated 30 years (1990–2019) of sightings data with carcass recovery and necropsy information (Moore et al, 2004; Sharp et al, 2019) and explicitly modeled the observation processes to improve inferences on mortality rate estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with high levels of mortality and serious injuries from human activities, low reproductive rates likely contribute to the decreasing population trend [23,24]. Using an individual-based state-space model for health, survival and reproduction, Pirotta et al [25] showed that female calving probability has been continuously declining over the last five decades. This model showed that calving probability was associated with the health metric, which also declined over time, but a large portion of the calving decline was ascribed to individual-level variability unrelated to health.…”
Section: Introductionmentioning
confidence: 99%
“…Using a subset of females in the population, Stewart et al [26] found a correlation between asymptotic body length and summary lifetime metrics of reproductive success (in particular, the number of births per reproductive year). Decreasing mean body size is therefore a good candidate trait for resolving the component of the decline in calving probability that was unrelated to concurrent health in the analysis of Pirotta et al [25]. However, relying on lifetime reproductive metrics is limiting, as it constrains the analysis to whales that have reproduced and thus excludes many of the smallest individuals in the dataset that have yet to reproduce [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation